Current Perspectives on the Strategic Future of the Poultry Industry After the COVID-19 Outbreak - Abdul Samad; Muhammad Hamza; Ayesha Muazzam; Areeb Ahmer; Sania Tariq; Shehroz Ahmad; M.Talha Mumtaz (Brilliance: Research of Artificial Intelligence, 2022)
The future expansion of the poultry business is hampered by a number of reasons, including chicken immunity, health, and productivity. Major obstacles to the present state of the sector and its strategic future will continue to be consumer confidence, product quality and safety, product kinds, and the introduction and re-emergence of illnesses. Poultry is inextricably related to zoonotic and foodborne illnesses. Foodborne and zoonotic pathogen eradication, elimination, and/or management provide a significant challenge to the chicken business. The risks to the general public's health from eating foods with significant antibiotic residues will also continue to be a major problem. This review's idea of chicken farming goes beyond only thinking about disease prevention. Instead, it will take into account how the immunity, wellbeing, and health of the animals are interconnected. It is crucial to understand that hens are not vulnerable to intranasal SARS-CoV-2 (COVID-19) viral infection. Nevertheless, the COVID-19 pandemic will have an impact on chicken farming's finances, transportation, and consumption. Along with these factors, it will evaluate the maintenance of high environmental security as well as economic, ethical, and social aspects. For the industry to meet consumer demand and guarantee sustainable agriculture, shareholders, veterinarians, farmers, and all other stakeholders in the chain of poultry production need to be more active in the present state and the sector's strategic future. The current evaluation examines these crucial activities as a result.